Escrita de si, gênero e suas intersecções nas crônicas “jornalisticamente incorretas” de Marilene Felinto - Sousa, Maria Aparecida Saraiva Magalhães de (2020)
This research work aims to develop a critical review of the genre ‘chronicle’, observing its proximity (or intimacy) with self-writing and women writing. We take the production of the contemporary writer Marilene Felinto, focusing the chronicles she published at Folha de São Paulo between 1995 and 1999, presented in the book entitled Jornalisticamente incorreto (2000). First, we present a feminist critical view on the construction of the genre chronicle as a literary genre (LIMA, 1986, 1992, 2003; MOISÉS, 1979; OCAÑA, 2008). We problematize the marginalizing of this genre in relation to other traditionally canonized ones, observing how the relation between history and women’s writing has been established along the centuries. Taking into account concepts discussed by feminist literary criticism, especially those resulting from an uncomfortable sensation of ‘author exclusion’ and proposing a re-vision of literary history (RICH, 1971; KOLODNY, 1979; SCHMIDT; 2017; DUARTE, 1995; MOREIRA, 2003, 2005, 2015). We emphasize some women writers who also wrote on this genre, mainly some Brazilian journalists from the past. After that, we discuss ‘autobiographic literature’ (ROCHA, 1977), so to better understand the hybridity of the genre, showing some exchanges it establishes with other forms of self-writing (FOUCAULT, 1992), while observing to what extend women writers were able to find a space in chronicles to elaborate their subjectivities, to denounce inequalities and resist imposed silencing (RÉGNIER-BORLER, 1994; RAMOS, 2008; KAPLAN, 1997; RAGO, 2011, 2013; FIGUEIREDO, 2013, GARRETAS, 1990). Finally, we take some important theoretical foundations of black feminism to support the reading of Felinto’s writing (CARNEIRO, 2000, 2003; GONZALEZ, 1984; hooks, 2017, 2018). In this sense, we reflect deeply on the intersections of gender with other categories related to the discussion of unequal power relations such as class and race as a way to analyze some of Marilene Felinto’s texts through the lenses of identity, problematizing the writing of this Afro-Brazilian woman from Pernambuco State.